Nutrition for foodservice and culinary professionals - Drummond, Karen Eich; Brefere, Lisa M. (Wiley, 2022)
In the newly revised 10th Edition of Nutrition for Foodservice and Culinary Professionals, registered nutritionist Karen E. Drummond and executive chef Lisa M. Brefere deliver an insightful guide to incorporating healthy, balanced dietary techniques into everyday practice. From national nutrition guidelines to food preparation and labeling standards, the authors cover every relevant aspect of planning, preparing, and serving healthy meals. They include updated 2020-2025 Dietary Guidelines for Americans from the USDA, the latest nutrition research, culinary trends, ingredients, and planning menus to meet the diverse nutritional needs of today's customers. This book also includes A thorough introduction to the fundamentals of nutrition and foods, including why nutrition is important, what constitutes a healthy diet, and discussions of calories and nutrients. A comprehensive exploration of balanced cooking and menus, including how to build flavor, balanced baking, modifying recipes, and gluten-free baking. Practical discussions of applied nutrition, including how to handle customers' special nutrition requests, weight management, and nutrition for people of all ages. Several appendices including serving sizes for MyPlate food groups and dietary reference intakes. An enhanced e-book with links to technique videos, interactive games, quizzes, and glossary entries. Perfect for students completing a culinary arts or foodservice management curriculum, Nutrition for Foodservice and Culinary Professionals, Tenth Edition is also an indispensable resource for chefs, cooks, and anyone else who professionally prepares food.